2011
DOI: 10.1016/j.taap.2010.11.015
|View full text |Cite
|
Sign up to set email alerts
|

MRP2 and the handling of mercuric ions in rats exposed acutely to inorganic and organic species of mercury

Abstract: Mercuric ions accumulate preferentially in renal tubular epithelial cells and bond with intracellular thiols. Certain metal-complexing agents have been shown to promote extraction of mercuric ions via the multidrug resistance-associated protein 2 (MRP2). Following exposure to a non-toxic dose of inorganic mercury (Hg 2+ ), in the absence of complexing agents, tubular cells are capable of exporting a small fraction of intracellular Hg 2+ through one or more undetermined mechanisms. We hypothesize that MRP2 play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 36 publications
4
37
0
Order By: Relevance
“…Oat1 supports organic anion/α-ketoglutarate exchange 34,35 . Several recent studies have demonstrated that Mrp2 plays an important role in the cellular elimination and secretion of certain mercuric species 10,31,36 . Mrp2 is localized exclusively in the apical plasma membrane of proximal tubule epithelial cells.…”
Section: -Results and Discussionmentioning
confidence: 99%
“…Oat1 supports organic anion/α-ketoglutarate exchange 34,35 . Several recent studies have demonstrated that Mrp2 plays an important role in the cellular elimination and secretion of certain mercuric species 10,31,36 . Mrp2 is localized exclusively in the apical plasma membrane of proximal tubule epithelial cells.…”
Section: -Results and Discussionmentioning
confidence: 99%
“…The export of mercuric species from within enterocytes, across the apical membrane, and into the intestinal lumen may be mediated by MRP2 ( ABCC2 ). MRP2 has been shown to be involved in the intestinal secretion of organic anions (Itagaki et al 2008) and has been implicated previously in the transport of mercuric ions (Bridges et al 2008a, b, 2011). Owing to the broad substrate specificity of MRP2 and MRP3, it is possible that they may be involved in the basolateral to apical movement of thiol S -conjugates of Hg 2+ across enterocytes.…”
Section: Transport Of Inorganic Mercurymentioning
confidence: 99%
“…A small fraction of mercuric ions are transported out of proximal tubular cells without the use of a chelating agent (Bridges et al 2011). However, the most efficient means of extracting mercuric ions from within target cells is through the use of a dithiol, metal chelator/complexing agent, such as 2,3-dimercapto-1-propanesulfonic acid (DMPS) or dimercaptosuccinic acid (DMSA; Fig.…”
Section: Transport Of Inorganic Mercurymentioning
confidence: 99%
See 1 more Smart Citation
“…No corresponding study was located which considered Pb. The two chemicals are also likely transported across the brain barrier via different transporters, MeHg via the neutral amino acid carrier and possibly the p-glycoprotein MDR2 (Yin 2008;Bridges, Joshee, and Zalups 2011) and Pb via the DCT (Ballatori 2002), although research in this area is far from complete. There are also known BBB maturation differences between rodents and humans, which would complicate quantitative interpretation of results from animal experiments (Calabrese 1983).…”
Section: Blood Brain Barrier Permeabilitymentioning
confidence: 99%